Anatomical Study of the Neurovascular in Flexor Hallucis Longus Tendon Transfers - Haijiao Mao (Nature Portfolio, 2017)
Abstract The transfer of the flexor hallucis longus tendon or flexor digitorum longus tendon is frequently used for the treatment of posterior tibial tendon insufficiency or chronic Achilles tendinopathy. According to several anatomical studies, harvesting the flexor hallucis longus (FHL) tendon may cause nerve injury. Sixty-eight embalmed feet were dissected and anatomically classified to define the relationship between Henry’s knot and the plantar nerves. Two different configurations were identified. In Pattern 1, which was observed in 64 specimens (94.1%), the distance between the medial plantar nerve and Henry’s knot was 5.96 mm (range, 3.34 to 7.84, SD = 1.12). In Pattern 2, which was observed in 4 specimens (5.9%), there was no distance between the medial plantar nerve (MPN) and Henry’s knot. No statistically significant difference was observed according to gender or side (p > 0.05). A retraction was performed to harvest the FHL through the posteromedial hindfoot incision using a single minimally invasive technique, and the medial and lateral plantar nerve lesions were scrupulously assessed. In conclusion, medial and lateral plantar nerve injuries did not occur more frequently, even after performing a single minimally invasive incision to harvest the FHL tendon, due to the large distance between the FHL tendon and the medial and lateral plantar nerves.